May the alterable use of the FIGO 1988 Staging System and the FIGO 2009 Staging System for endometrial cancer lead to significant clinical mistakes? (Menopause Review/Przegląd Menopauzalny, 2011)

(untitled) - Gottwald, Leszek; Moszyńska-Zielińska, Małgorzata; Surkont, Grzegorz; Korczyński, Jerzy; Tyliński, Wiesław; Szwalski, Jarosław; Spych, Michał
Introduction : Since 2009 the new FIGO Staging System of endometrial cancer, which changed the previous FIGO 1988 Staging System, has been present. Unfortunately, parallel use of both classifications is observed. Aim of study : to assess whether parallel use of the 2009 and the 1988 FIGO staging systems can cause significant therapeutic mistakes in patients with endometrioid endometrial cancer. Material and methods : We analysed 262 patients with endometrioid endometrial cancer. The endometrial cancers were staged in both classifications. We analysed possible therapeutic mistakes caused by diverse nomenclature. Results : The patients at low risk, intermediate risk, and high risk for relapse were presented in: 110 (41.6%), 109 (42.0%) and 43 (16.4%) cases, respectively. The possibility of inappropriate qualification for adjuvant treatment occurred in 102 patients (38.9%) if they were staged in the FIGO 1988 classification and interpreted as the FIGO 2009 classification, and similarly, in 65 patients (24.8%) if they were staged in the FIGO 2009 classification and interpreted as the FIGO 1988 classification. The risk of a decision mistake in terms of the adjuvant treatment due to diverse nomenclature was observed commonly in 167 patients (63.7%). Conclusions : The common use of both FIGO staging systems for endometrioid endometrial cancer can cause significant therapeutic mistakes in terms of the adjuvant treatment. There is a need to use only the new FIGO 2009 Staging System for endometrial cancer and stop using the FIGO 1988 Staging System to avoid therapeutic mistakes.